Phenolic and Aroma Composition of White Wines Produced by Prolonged Maceration and Maturation in Wooden Barrels - Nikolina Jedrejčić (Food Technology and Biotechnology, 2015)
To investigate the phenolic and aroma composition of Malvazĳa istarska (Vitis vinifera L.) white wines produced by an unconventional technology comprising prolonged maceration followed by maturation in wooden barrels, representative samples were subjected to analysis by UV/Vis spectrometry, high-performance liquid chromatography, and gas chromatography-mass spectrometry. When compared to standard wines, the investigated samples contained higher levels of dry extract, volatile acidity, lactic acid, phenols, colour intensity, antioxidant activity, majority of monoterpenes, C13-norisoprenoids, methanol, higher alcohols, ethyl acetate, branched-chain esters and esters of hydroxy and dicarboxylic acids, ethylphenols, furans, and acetals, as well as lower levels of malic acid, β-damascenone, straight-chain fatty acids, ethyl and acetate esters. It was estimated that maceration had a stronger influence on phenols, and maturation on volatile aromas. Despite different vintages and technological details, the investigated wines showed a relative homogeneity in the composition, representing a clear and distinctive type.